Prothrombin activator-like toxin appears to mediate cardiovascular collapse following envenoming by Pseudonaja textilis. (August 2015) - Chaisakul, Janeyuth; Isbister, Geoffrey K.; O'Leary, Margaret A.; Parkington, Helena C.; Smith, A. Ian; Hodgson, Wayne C.; Kuruppu, Sanjaya
Abstract: Brown snake ( Pseudonaja spp.)-induced early cardiovascular collapse is a life-threatening medical emergency in Australia. We have previously shown that this effect can be mimicked in animals and is mediated via the release of endogenous mediators. In the present study, we aimed to purify and characterize the component in Pseudonaja textilis venom which induces cardiovascular collapse following envenoming. The component (fraction 3) was isolated using a combination of techniques including hydroxyapatite and reverse phase chromatography. Fraction 3 (10 or 20 μg/kg, i.v.) produced a rapid decrease in mean arterial pressure (MAP) followed by cardiovascular collapse. Fraction 3-induced early collapse was abolished by prior administration of smaller priming doses of fraction 3 (i.e. 2 and 5 μg/kg, i.v.) or heparin (300 units/kg, i.v.). P. textilis whole venom (1 and 3 μg/ml), but not fraction 3 (1 or 3 μg/ml), induced endothelium-dependent relaxation in isolated rat mesenteric arteries. SDS-PAGE gel indicated the presence of 9–10 protein bands of fraction 3. Using proteomic based analysis some protein bands of fraction 3 were identified as subunits of venom prothrombin activator, pseutarin C of P. textilis venom. Our results conclude that prothrombin activator-like toxin is likely to be a contributor to the rapid collapse induced by P. textilis venom. Highlights: Fraction 3 identified in this study is the same as previously identified pseutarin C. Pseutarin C mediates cardiovascular collapse following envenoming by Pseudonaja textilis. Prior administration of lower doses of pseutarin C prevents sudden drop in MAP in response to a large dose. Effect of pseutarin C on blood pressure can be blocked by heparin. Pseutarin C has no effect on mesenteric artery relaxation and has very low PLA2 activity.